Teachers’ Perception about Authentic Assessment of English Learning Based on Merdeka Curriculum: A Case in Papua - Arjuna, Ricky; Hikmat, Mauly Halwat; Candraningrum, Dewi (AL-ISHLAH: Jurnal Pendidikan, 2024)
Students who continue to struggle with English proficiency suggest that the use of realistic assessment in classroom instruction is subpar. As a result, the purpose of this study is to investigate the barriers to and facilitators of real assessment in the classroom and the gap between instructors' conceptions of the concept and its actual use. The research strategy used in this study is a qualitative one, namely descriptive research, and the data gathering tools include interviews and observations of English instructors in Manokwari. Two high school English instructors participated in this study. The results of this research indicate that teachers in Papua have a good understanding of authentic assessment as indicated by various detailed explanations of authentic assessment by teachers. The results obtained from interviews and observations in the implementation show the process of preparing assessments and various types of authentic assessments carried out by teachers in the classroom. However, in carried out the assessment, some of the problems faced by the teacher included the inability to manage the class, determine the assessment items and limited of time. Based on the results of interviews and observations conducted, there is a match between understanding and implementation, meaning that there is no discrepancy between understanding and implementation in class.